L’impact de la politique de gestion de l’entreprise dans le discours organisationnel - Manceau, Amelia (Studia Romanica Posnaniensia, 2019)
Global internationalization of companies is a new challenge in the area of management and brings about changes in communication. Organizational discourse in corporations remains a still unexplored research domain. The multilingual population working within the same corporation organization is creating its own language that becomes a kind of jargon giving rise to misunderstandings outside of the workplace. We want to emphasize mutation of the corporate language in the synchronic approach. We analyse emails, oral conversations, as well as instantaneous written conversations, etc. Special attention is paid to anglicisms, tutoiement and imperative structures.